Design and implementation of a Community Expert Group comprised of people with lived expertise of homelessness at an academic health research center: a program description and analysis of challenges - Ayan A. Yusuf; Victoria Hatfield; Katherine Francombe Pridham; George Da Silva; Rene Adams; Daniela Mergarten; Veronica Snooks; Frank Crichlow; Stephen W. Hwang (Research Involvement and Engagement)
Abstract The involvement of communities with a stake in healthcare research is often limited, and attempts to increase their participation and to create shared decision-making partnerships are often hindered by structural barriers. In this paper, we describe the design and implementation of a Community Expert Group comprised of people with lived expertise of homelessness at an academic health research center. We detail the group’s model, guiding principles, governance structure, and activities, and discuss institutional challenges encountered over the course of this partnership. We report that the lack of policies and practices in academic research institutions to support long-term collaboration with community experts makes it challenging to define their scope and role, often requiring individual research teams to fill this gap.